Statistical characteristics of 750-Hz band ELF emissions observed at Syowa Station - Ito, Kodo; Shibuya, Senkichi; Maezawa, Kiyosh; Sato, Natsuo (1986)
P(論文) The digital recording system of ELF-VLF emissions was installed at Syowa Station, Antarctica (L=6.1) in 1981. With the digital data recorded from June 1981 to January 1983,statistical characteristics of emission occurrences at a 750-Hz band were examined. The noticeable occurrence distributions depending on diurnal variation, seasonal variation, and Kp indices are found. We discussed some reasons of the seasonal variation effects. departmental bulletin paper